(untitled) (Scientific journal of the Fergana State University, 2024)
In the article, for students involved in athletics, during training sessions in school conditions, special exercises were conducted related to the development of their physical qualities, including non-traditional exercises related to rotational accelerations and new innovative methods (styles) and it is proved that regular use under the influence of action games leads to effective results.